A prospective study to validate the functional assessment of cancer therapy (FACT) for epidermal growth factor receptor inhibitor (EGFRI)-induced dermatologic toxicities FACT-EGFRI 18 questionnaire: SWOG S1013 - Siu-Fun Wong; Joseph M. Unger; James L. Wade; Lynne I. Wagner; Mario E. Lacouture; Keisha C. Humphries; Anna Moseley; Kathryn Arnold; Mario R. Velasco; Justin D. Floyd; Benjamin T. Esparaz; Afsaneh Barzi; et al. (SpringerOpen, 2020)
Abstract Background Papulopustular rash is a common class effect of epidermal growth factor receptor inhibitors (EGFRI) that can affect patients' health-related quality of life and cause disruptions to treatment. SWOG S1013 (NCT01416688) is a multi-center study designed to validate the Functional Assessment of Cancer Therapy EGFRI 18 (FACT-EGFRI 18) using 7-items from the National Cancer Institute (NCI) Common Terminology Criteria for Adverse Events (CTCAE) version 4.0 to assess EGFRI-induced skin-related toxicities and their impact on functional status. Methods Patients with a diagnosis of colorectal or lung cancer to receive EGFRI therapies for at least 6 weeks were enrolled. Patient self-assessments using the FACT-EGFRI 18 were completed prior to undergoing CTCAE assessment by trained clinicians at baseline, weekly × 6, and then monthly × 3. The psychometric properties of the FACT-EGFRI 14 (skin toxicity items only) and 18 (plus 2 nail and 2 hair items) were established based on criterion validity, known groups validity, internal consistency reliability, and responsiveness to change. Results Of the 146 registered patients, 124 were evaluable. High Cronbach's alpha (> 0.70) for both FACT-EGFRI 14 and FACT-EGFRI 18 scores across assessment times were observed. Although agreement (i.e. criterion validity) between individual and summary scales of the FACT-EGFRI 18 for assessing skin toxicity was good, agreement with the clinician-reported CTCAE was only fair. The minimal important difference was determined to be 3 points. The results also demonstrated responsiveness to symptom change. Discussion Based on the results of this multi-center validation study, the FACT-EGFRI 18 patient-reported outcome instrument provided data from the patient's perspective yielding unique information as well as complementing clinician-rated CTCAE grades, especially for the symptoms of pain, pruritus, and paronychia. Conclusions Good to excellent psychometric properties for the FACT-EGFRI 18 were demonstrated, supporting further use of this patient-reported outcomes measure. Additional validation with a more diverse group of patients should be conducted.